TERMITES SPECIES RICHNESS AND DISTRIBUTION AT RESIDENTIAL AREA IN PT ARUN LNG - Syaukani Syaukani (Universitas Syiah Kuala, 2013)
Termites were collected in June 2012 at residental area of Pt. Arun LNG by adopted casual collection and finding colony methods. Six species and four genera had been identified to belong to the higher termites (Kalotermitidae and Rhinotermitidae) and had been collected from different habitats throughtout the residential area. Those species randomly distributed which the highest species richness found at Tarakan (6 species). Residential condition with poor maintenance was contributes to inhabitant of the termites to harbour there. One of the most destructive species, Coptotermes curvignathus, has been found to attacking building as well as plants.